Peningkatan Keterampilan Menulis Narasi Menggunakan Model Picture And Picture pada Siswa Kelas IV SD - Yani, Rini; Eliyasni, Rifda; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of narrative writing skill using Picture And Picture model in fourth grade students of SD Negeri 08 Pisang Kota Padang. Research subjects are teachers as observers, researchers, and students of class IV as many as 25 people consisting of 15 women and 10 men. In the pre-cycle I obtained an average score of 74.0 %, the average value of writing 41.0%, and the average post-writing value of 43.0%. In cycle II, the average pre-writing score of 94.0%, the average value of writing is 86.0%, and the post-writing average is 87.5%. Thus writing a narrative using the Picture and Picture model can improve student learning outcomes in grade IV SD Negeri 08 Pisang Kota Padang  Keywords: narrative writing, Picture And Picture